弧齿锥齿轮磨削表面烧伤建模仿真与实验验证 - 明兴祖; 李飞; 周静 (Jixie chuandong)
By using the theoretical derivation,the method of combining numerical simulation method with modern experimental means,firstly,through SG grinding wheel,the finite element model of temperature field of 20CrMnTi spiral bevel gear tooth form grinding is established,the temperature field simulation analysis is carried out by using rectangular distribution of heat source method of moving load and ANSYS software.The influence law of different grinding parameters on the distribution of temperature field of grinding process is got.Namely with the increase of grinding depth, the temperature of workpiece surface temperature in the grinding zone rises,grinding wheel linear velocity is higher,the grinding temperature rises.With the increment of generating speed,the graph showed a trend of increasing after the first reducing of the grinding temperature and maximum temperature are located around grinding arc center.Then,the color and morphology of spiral bevel gear wheel burns surface is observed.By observing the microstructure of burn area,the organization on the surface of quenching burn area is troostite.When moderate burn of the burn area,the organization at the outer surface of the secondary quenching martensite,the bottom of quenching burn area is tempered martensite or sorbite.When serious burn of the burn area,the organization at surface is sorbite.Finally,it is found that when the gear in slight burns,the surface microhardness significantly below the hardness before grinding,the metamorphic layer depth is greater than 0.2mm,when severe burns,annealing burn surface and surface hardness drop more,the metamorphic layer depth increased,and the more severe burns,the more fall of surface micro hardness.It is concluded that,when the metamorphic layer depth is greater than 0.2mm,different degree of grinding burn is produced.